PERILAKU MEMILIH MASYARAKAT DESA PADA PEMILIHAN KEPALA DESA (STUDI KASUS DESA NGADAS KABUPATEN MALANG) - Carissa Nabila Harijadi; Nabila Raudhana; Raihan Atthalah; Diva Brilliana; Ratnia Solihah (UNES Law Review, 2023)
The election of the village head is a form of democracy in the local political sphere of the village. This study focuses on voting behavior in village head elections in Ngadas Village, Malang Regency, which has a diversity of religions in its community. In addition to knowing whether religious factors influence voting behavior, this research also examines the possibility of other factors influencing the voting behavior of the people of Ngadas Village at the time of the village head election. To obtain information and data to answer the above, the researchers conducted a field study to Ngadas Village, Malang Regency by conducting interviews and documentation through a qualitative research approach. The informants interviewed consisted of the Village Head, Traditional Leaders, and several residents of Ngadas Village. Based on the results of field research, the voting behavior of the people of Ngadas Village was not influenced by religious diversity, but was more influenced by the figure of the village head candidate and the capacity of the village head candidate in carrying out the program as well as the vision and mission carried out during the village head election campaign. Thus, the voting behavior of the community in the election of the head of Ngadas Village tends to be based on psychological factors and rational choice factors.